Study on the employee job performance in tourism industry: A case study at Mahkota Hotel Melaka / Nur Athirah Yahya and Shafinaz Mohd Izhar - Yahya, Nur Athirah; Mohd Izhar, Shafinaz (Faculty of Administrative Science and Policy Studies, 2013)
This research is about a study on the employee job performance in the tourism industry at Mahkota hotel Melaka. The objectives of this research are to measure the level of job performance, to measure the level of factors that affect job performance, and to determine the relationship between motivation, ethic knowledge, accountability, and workplace environment with job performance. 170 respondents were selected as a sample size of this research. Simple random sampling technique was used when selected the 170 respondents at Mahkota Hotel Melaka. The respondents were required to answer questionnaire that consist of 3 sections with 48 questions. The researcher use Descriptive Statistic, Cronbach’s Alpha and Peason Rank Order Correlation to analyze the data gathered by using Statistical Package for Social Science (SPSS) version 20.0. The result indicates that the level of individual performance is good and the employees agreed that they have a good level of motivation, ethic knowledge, accountability, and workplace environment. In addition, there are positive correlation between all four factors which are efforts motivation, skills ability, role perceptions, and organizational resources with individual’s performance. The most influential factor that affects job performance at Mahkota Hotel Melaka is skills and ability with the significant value in regression test is 0.020.